Production of Mg-Li alloys by aluminothermic vacuum reduction - Wang Y.-W.; You J.; Wang A.-G.; Peng J.-P.; Di Y.-Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Mg–Li alloys are the lightest metallic construction materials and one of the most representative light alloys. The process of producing Mg–Li alloys by vacuum aluminothermic reduction, using magnesite and lithium carbonate as raw materials, was studied. The influence of reduction parameters on the extents of reduction of MgO and Li2O was investigated. The results show that Mg–Li alloys can be produced by vacuum aluminothermic reduction using calcined magnesite and lithium carbonate. MgO was relatively easier to reduce by aluminum than Li2O. Almost all MgO was reduced to Mg and more than 96% of Li2O was reduced to Li. The main phase in the reduction slag was Li2O•5Al2O3. The reaction mechanism was discussed. Vacuum aluminothermic reduction can be considered as a highly efficient and environmental friendly method for producing Mg–Li alloys.